The merge : a novel - Walker, Grace, 1994- (Mariner Books, 2025)
"How far would you go to never say goodbye? Laurie is sixty-five and living with Alzheimer's. Her daughter Amelia, a once fiery and strong-willed activist, can't bear to see her mother's mind fade. Faced with the reality of losing her forever, Amelia signs them up to take part in the world's first experimental merging process for Alzheimer's patients, in which Laurie's ailing mind will be transferred into Amelia's healthy body and their consciousness will be blended as one. Soon Amelia and Laurie join the opaque and mysterious group of other merge participants: teenage Lucas, who plans to merge with his terminally ill brother Noah; Ben, who will merge with his pregnant fiancée Annie; and Jay, whose merging partner is his addict daughter Lara. As they prepare to move to The Village, a luxurious rehabilitation center for those who have merged, they quickly begin to question whether everything is really as it seems. An exhilarating, immersive debut from an astonishing new voice, THE MERGE is a personal story of love, family, and sacrifice, as well as a thought-provoking examination of the limits of control, resistance, and freedom in our modern world"--